Efek Adultisida Minyak Atsiri Bunga Cengkeh (Syzygium aromaticum) Sebagai Bahan Anti Nyamuk Elektrik Terhadap Nyamuk Aedes Aegypti - Muhammad Faris - (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
ABSTRACT Background: Liquid vaporizer was preserved by people, but the chemical insecticide caused an impact on the environment and health. The essential oil of clove flower was proved as an insecticide against Aedes aegypti, so it can be developed as an alternative to control the dengue vector in liquid vaporizer form. Objective: To know effect adulticide of clove flower essential oil as an electrical liquid vaporizer agent against Aedes aegypti Method: This research is a true experimental study with a post-test only with control group design. This research consists of 2 control and 4 test groups with the variant concentration of flower clove essential oil 12 %, 27%, 48%, 79 %. Mosquitoes are exposed for 60 minutes then transfer to the holding tube and left for 24 hours. Finally, the percentage of mortality was calculated. The test was repeated four times and the results were analyzed using Kruskal Wallis and Probit test. Result: The average percentage of mosquito mortality in negative control, positive control, concentration of 12%, 27%, 48% and 79% were 0%, 100%, 8%, 33% respectively. The statistical test of p =0,011 (p<0.05) with probit shows LC50 = 5,288 and LC90 = 7,837. Conclusion: Clove (Syzygium aromaticum) flower essential oil had a potential adulticide effect against Aedes aegypti in the form of an electrical liquid vaporizer agent. Keywords: Aedes aegypti, clove, electrical liquid vaporizer, essential oil